Konflik Komunikasi Kelompok Pecinta Klub epak Bola Persija (Jakmania) di Medan - Rendy Grimaldi Valeri; Syafruddin Ritonga; Novri Novri (Jurnal Ilmu Pemerintahan, Administrasi Publik, dan Ilmu Komunikasi (JIPIKOM), 2022)
The purpose of this study was to find out the beginning of the Communication Conflict of PERSIJA’s Football Club Lovers (Jakmania) in Medan and to found out how to overcome the communication conflict of PERSIJA’s Football Club Lovers (Jakmania) in Medan. This research used qualitative research methods. The results showed that the communication conflict that occurred in The Jakmania Medan is started from hateful comments made by other supporters to PERSIJA on social media and then caused a sense of revenge in the members of The Jakmania Medan. This led to differences of opinion between members of The Jakmania Medan, members who approved of to take revenge in social media comments and members who did not approve of it. This difference of opinion can even caused fights among fellow members of The Jakmania Medan while arguing to convey each of their opinion. The role of the group Leaader related is efforts to overcome communication conflicts that occur in The Jakmania Medan is by mediating and sanctioning. The form of sanctions that will be given is the revocation of member identification cards (KTA) and sanctions in the form of legal forms.